2009
DOI: 10.1007/s10526-009-9209-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative efficacy assessment of fungi, nematodes and insecticides to control western corn rootworm larvae in maize

Abstract: All three larval instars of Diabrotica virgifera virgifera LeConte (western corn rootworm, Coleoptera: Chrysomelidae) feed on the roots of maize, Zea mays (L.). We assessed the efficacies of the following four agents in controlling these larvae: (1) the entomopathogenic fungus Metarhizium anisopliae (Metsch.) Sorokin (Hypocreales: Clavicipitaceae), (2) the nematode Heterorhabditis bacteriophora Poinar (Nematoda: Rhabditida), (3) a tefluthrin-based soil insecticide and (4) clothianidin-coated seeds. The agents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
40
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 64 publications
(69 reference statements)
4
40
0
Order By: Relevance
“…2). Field studies employing the entomopathogen species used in the current study have shown decreased survival of rootworm in a number of cases (Krueger and Roberts 1997;Journey and Ostlie 2000;Toepfer et al 2008Toepfer et al , 2010Pilz et al 2009). However, entomopathogen efÞcacy, particularly with nematodes, has also been shown to be variable and sometimes inconsistent under Þeld conditions, and can depend on many factors including environmental conditions, application method, concentration, and strain (e.g., Wright et al 1993, Jackson and Brooks 1995, Riga et al 2001.…”
Section: Discussionmentioning
confidence: 71%
“…2). Field studies employing the entomopathogen species used in the current study have shown decreased survival of rootworm in a number of cases (Krueger and Roberts 1997;Journey and Ostlie 2000;Toepfer et al 2008Toepfer et al , 2010Pilz et al 2009). However, entomopathogen efÞcacy, particularly with nematodes, has also been shown to be variable and sometimes inconsistent under Þeld conditions, and can depend on many factors including environmental conditions, application method, concentration, and strain (e.g., Wright et al 1993, Jackson and Brooks 1995, Riga et al 2001.…”
Section: Discussionmentioning
confidence: 71%
“…In the small cup assay, H. bacteriophora and S. feltiae were applied at an average rate of 4.7 ϫ 10 9 nematodes per hectare and imposed an average of 39 and 46% mortality, respectively (Table 3). Metarhizium anisopliae imposed 31% mortality against western corn rootworm when applied in the Þeld at a range of 4 ϫ 10 13 to 7 ϫ 10 13 conidia per hectare (Pilz et al 2009). In the small cup assay reported here, M. brunneum and B. bassiana were applied at an average rate of 3.5 ϫ 10 12 conidia per hectare and imposed an average 9 and 11% mortality, respectively (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…Seed coating or granular insecticides are the usual methods of soil pest control in maize monoculture, and clothianidin and tefluthrin are often used to control this pest (Pilz et al, 2009). Before the invasion of D. v. virgifera to Slovakia, the chemical control of maize soil pests was only used sporadically because of elaterid larvae.…”
Section: Introductionmentioning
confidence: 99%
“…Communities of nematodes are frequently used as suitable bioindicators based on their occurrence in all types of soil, a high abundance and the presence of all trophic groups. Earlier studies on nematodes in maize throughout the world were focused mostly on plant-parasitic nematodes that feed on maize (Bernard et al, 2010;Bowen et al, 2008;Tylka et al, 2011) or the impact of crop rotation on nematode communities (Drake et al, 2010;Manachini et al, 2009;Rahman et al, 2007;Villenave et al, 2009). It was also mentioned that low infections of plant-parasitic nematodes may lead to greater availability of plant nutrients .…”
Section: Introductionmentioning
confidence: 99%